Analysis of Downstream Flood Risk in the Failure of Batman Dam with Two-Dimensional Hydraulic Modeling and Satellite Data - Gökçen Uysa; Enver Taşçı (Doğal Afetler ve Çevre Dergisi)
It is important to determine the flood effects due to dam break on the downstream region for disaster preparedness studies. In this work, the flood risk potential of the residential area located downstream of Batman Dam was investigated. The study consists of two phases which are integrated within the HEC-RAS model. In the first stage, the flood hydrograph as a result of the dam break was obtained considering a trapezoidal breaching of the dam body. In the second stage, the propagation of the flood was simulated in the Batman River and its nearby area using a 2-Dimensional hydrodynamic model. Terrain information, which is the most important input of the model, was obtained from Digital Elevation Model (DEM) based satellite product data using SRTM with 30 m spatial resolution and ALOS-PALSAR with 12.5 m spatial resolution. The results (water depth, water speed, arrival time and hazard maps) were compared with the 5 m spatial resolution Digital Surface Model (DSM) based reference model results provided by the General Directorate of Maps. The flood reaches Batman Airport within 3-4 hours and the water velocities in the river bed vary between 5-10 m/s. Satellite DEM-based models can produce results close to the reference model (R2=0.79). According to the maximum water level F-index performance, the similarity between the reference model is around 92%. Despite its low spatial resolution, SRTM satellite has lower/similar error values (RMSE and MAE) compared to ALOS-PALSAR. The flood does not reach the city, but it may have a partial effect on the Wastewater Treatment plant and Batman Airport. Also, it is predicted that 10,985 people in rural areas will be affected by the flooding risk.